Chemical and Pharmacological Properties of the Cashew Tree (Anacardium Occidentale): A Review (REMUNOM, 2024)
Cashew, belonging to the Anacardiaceae family, of the species Anacardium occidentale, is a tropical pseudofruit, of Brazilian origin and from the Amazon region. It is a plant resistant to different climatic and environmental conditions, which is characteristic of Cerrado. A. occidentale has a wide range of secondary metabolites, according to phytochemical research. Phytochemical substances such as triterpenoids, phenolics, and volatile oils can be found in the ethanolic extract of A. occidentale L. nuts. A by-product of the cashew tree, which is also widely used, is its gum, which has healing activity, verified through tests on lesions, where a reduction in edema and hyperemia was observed, in addition to promoting a more accelerated appearance of local scar tissue. In cosmetology, there are already studies on the development of particles from parts of the cashew tree, and isolating some of its active ingredients, such as vitamin E, and applying them in formulations.